Lethal and nonlethal murine malarial infections differentially affect apoptosis, proliferation, and CD8 expression on thymic T cells. (July 2015) - Khanam, S.; Sharma, S.; Pathak, S.
Summary Although thymic atrophy and apoptosis of the double‐positive (DP) T cells have been reported in murine malaria, comparative studies investigating the effect of lethal and nonlethal Plasmodium infections on the thymus are lacking. We assessed the effects of P. yoelii lethal (17XL) and nonlethal (17XNL) infections on thymic T cells. Both strains affected the thymus. 17XL infection induced DP T‐cell apoptosis and a selective decrease in surface CD8 expression on developing thymocytes. By contrast, more severe but reversible effects were observed during 17XNL infection. DP T cells underwent apoptosis, and proliferation of both DN and DP cells was affected around peak parasitemia. A transient increase in surface CD8 expression on thymic T cells was also observed. Adult thymic organ culture revealed that soluble serum factors, but not IFN‐γ or TNF‐α, contributed to the observed effects. Thus, lethal and nonlethal malarial infections led to multiple disparate effects on thymus. These parasite‐induced thymic changes are expected to impact the naïve T‐cell repertoire and the subsequent control of the immune response against the parasite. Further investigations are required to elucidate the mechanism responsible for these disparate effects, especially the reversible involution of the thymus in case of nonlethal infection.